2003
DOI: 10.1002/jnr.10745
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic processing of the Alzheimer's disease amyloid precursor protein in brain and platelets

Abstract: Proteolytic processing of the amyloid precursor protein by beta -and gamma-secretases results in the production of Alzheimer's disease (AD) Abeta amyloid peptides. Modulation of secretase activity is being investigated as a potential therapeutic approach. Recent studies with human brain have revealed that the beta-secretase protein, BACE, is increased in cortex of AD patients. Analysis of betaCTF (or C99), the amyloid precursor protein (APP) product of BACE cleavage that is the direct precursor to Abeta, shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 63 publications
(77 reference statements)
6
100
0
2
Order By: Relevance
“…Concentrations of Aβ in cerebrospinal fluid (CSF) are at least 5-15 times higher than those in plasma 7,8 . One possible interpretation is that APP processing in peripheral cells probably occurs via α-cleavage (rather than the β-cleavage used in neurons) 9,10 , resulting in decreased peripheral production of Aβ. Another explanation for the lower Aβ levels in the periphery is that the periphery contains abundant Aβ-binding proteins (lipoproteins and albumin) 11 and Aβ-binding cells, such as erythrocytes 12 , which all contribute to Aβ transportation and clearance.…”
mentioning
confidence: 99%
“…Concentrations of Aβ in cerebrospinal fluid (CSF) are at least 5-15 times higher than those in plasma 7,8 . One possible interpretation is that APP processing in peripheral cells probably occurs via α-cleavage (rather than the β-cleavage used in neurons) 9,10 , resulting in decreased peripheral production of Aβ. Another explanation for the lower Aβ levels in the periphery is that the periphery contains abundant Aβ-binding proteins (lipoproteins and albumin) 11 and Aβ-binding cells, such as erythrocytes 12 , which all contribute to Aβ transportation and clearance.…”
mentioning
confidence: 99%
“…The inhibitory effect of ATRA on A␤ accumulation is likely attributable to its inhibition of APP processing, because the production of APP-CTFs, the direct precursor of A␤ (Evin et al, 2003), was attenuated by the ATRA treatment. In addition, a previous study has shown that ATRA prevents formation of fibrillar A␤ from fresh A␤ (Ono et al, 2004), suggesting that ATRA is involved in multiple steps of A␤ deposition.…”
Section: Discussionmentioning
confidence: 99%
“…APP is cleaved by BACE1 enzyme at the N-terminal region, producing membrane-bound C-terminal fragments (APP-CTFs) (Evin et al, 2003). APPCTFs are considered potential early markers for the biological diagnosis of AD (Sergeant et al, 2002).…”
Section: Atra Prevents App Processing and Phosphorylation Of Both Appmentioning
confidence: 99%
“…The dams that received the methionine supplement (DSD) showed, after twenty days of treatment, an increase in Hcy concentration of approximately 100% (8.71 µmol/L) compared to the control group (DCT) (4.45 µmol/L) (t (11) =5.59, p<0.001) (Figure 1). …”
Section: Damsmentioning
confidence: 99%
“…Amyloid-beta (Aβ) brain deposits are one of the hallmarks of the neuropathological degeneration observed in AD patients, and Aβ is produced by two sequential proteolytic cleavages of amyloid precursor protein (APP). APP can be processed by α-secretases (PS1 and PS2) and γ-secretases (ADAM10 and TACE) producing non-amyloidogenic peptides, or by α-secretases and β-secretases (BACE) producing the Aβ fragments [11][12][13]. PS1 and BACE are regulated by methylation and decreased folate and vitamin B12 in culture media can cause a decrease in S-adenosylmethionine (SAM), a universal donor of methyl groups, and an increase Aβ concentration [14].…”
Section: Introductionmentioning
confidence: 99%